Aspectos estatísticos em dinâmica de busca em ambientes escassos. - Faustino, Caio Leite (2009)
In this work, we analyze search dynamics and the statistical properties of an organism in search of a target of interest. In general terms, there are many interesting aspects of studies of this nature. For example, in the biological context, organisms in Nature constantly interact one with another, both of the same as well as of different species. The general objectives of random searches are diverse, ranging from searches for food, reproductive partners, etc. of living organisms to socio-economically relevant processes, such as searches for missing children, fugitive terrorists, or searches for petroleum. In our specific model, we consider the searcher and the target moving randomly in a one dimensional lattice of size with periodic boundary conditions. The type of diffusion in the system is determined by the choice of the probability distribution function for the steps sizes for the individual walkers. We assume a power law distribution, characteristic of Levy processes, . Considering an initial energy for the searcher, an energetic expenditure for the walk and an energetic gain g for each target found, we discuss relevant physical quantities, such as energy fluctuations, the fraction of survival searchers and the cumulative energy for N time steps, as a function of the parameters, e.g., the lattice size . We find that searches with ballistic diffusion are more efficient than Brownian ones, allowing the survival of the searcher in situations of ultra-low target density. This extreme behavior guarantees the differential survival of such searchers. We also find strong evidence of a continuous phase transition, in which one phase has survival and the other phase has extinction. We calculate the critical densities which depend on the parameters of diffusion adopted by the organisms. We also obtain the critical exponents for the transition. Our results suggest a universality of the critical exponents, which independent of the type of diffusion of the organisms.